A caring science study about the understanding of life and creative writing - Johanna Sandbäck Forsell; Linda Nyholm; Camilla Koskinen (JOURNAL OF POETRY THERAPY, 2023)
Creative writing is a known valuable aid for reflection on one’s life and involves the human being in a holistic way. This article has a caring science perspective and focuses on the understanding of life when creative writing is used to tackle unforeseen change. The unsolicited narratives of three authors were analysed in a study. The included texts were published autobiographical works and creative writing guides. A thematic network analysis was used as a method of analysis. The analysis ended up in a global theme that shows the understanding of life as a humble stance towards its changefulness. This theme entails acknowledging the uncertainty in life, seizing of opportunities and transformation through suffering. Creative writing is found to aid the human being to handle the changefulness of life